Psychosocial Correlates of Exclusive and Dual Nicotine Use among Adolescents in a Context of E-Cigarette Sales Prohibition - Barbara de Freitas Quitério; Patricia Paiva de Oliveira Galvão; Sheila Cavalcante Caetano; Zila M. Sanchez; Juliana Y. Valente (Journal of Community Health, 2026)
Abstract Although the sale of electronic cigarettes (ECs) has been prohibited in Brazil since 2009, experimentation among adolescents has increased substantially in recent years. Understanding the psychosocial factors associated with different nicotine use patterns in this regulatory context may help inform more effective prevention strategies. This study examined sociodemographic characteristics and psychosocial factors associated with exclusive EC use, exclusive conventional cigarette use, and dual use among Brazilian adolescents. A cross-sectional school-based survey was conducted with 2,939 adolescents from public schools in São Paulo State, Brazil. Participants completed an anonymous self-administered questionnaire. Multilevel multinomial logistic regression models were used to examine factors associated with exclusive EC use, exclusive conventional cigarette use, dual use, and non-use. The lifetime prevalence of exclusive EC use, exclusive conventional cigarette use, and dual use was 13.3%, 2.9%, and 12.9%, respectively. Girls were more likely to report exclusive EC use (RRR = 1.48; 95% CI: 1.16–1.88) and dual use (RRR = 1.52; 95% CI: 1.20–1.93), whereas boys were more likely to report exclusive conventional cigarette use. Perceived peer use and ease of access were strongly associated with both exclusive EC use and dual use, with consistently stronger associations among dual users. Adolescents who believed that ECs help reduce cigarette smoking were more likely to report exclusive EC use and dual use, whereas perceiving ECs as highly addictive was associated with lower odds of both exclusive EC use (RRR = 0.49; 95% CI: 0.35–0.67) and dual use (RRR = 0.44; 95% CI: 0.25–0.77). Psychosocial factors were differentially associated with nicotine use patterns among adolescents living in a context where EC sales are prohibited. These findings have important implications for community- and school-based prevention initiatives by highlighting the need to address perceived accessibility, peer norms, and misconceptions about electronic cigarettes in addition to regulatory measures.